El proceso de elaboración de piezas de teatro científico en la formación inicial de profesores de química - De Souza Pereira, Ademir (Tecné, Episteme y Didaxis: TED, 2018)
Scientific theater is an activity that involves theater scenarios based on scientific concepts aimed at the popularization of science and the scientist’s work. In this context, the purpose of this work was to investigate the educational process carried out in orientation meetings, in which different plays about scientific topics were created. We analyzed the researcher’s field diary as a result of two interventions: one with 12 students from the biology and chemistry course at Universidad Federal do Oeste de Pará (ufopa) and another one with 30 students from the chemistry course at Universidad Federal da Grande Dourados (ufgd), who created a total of 17 plays between 2013 and 2016. The field diary of the researcher, considered as a corpus, was submitted to the discursive textual analysis that made it possible for three categories to emerge: training meetings, experiment, and accessories. As a result, it was concluded that the educational process is present in the training and orientation meetings, in the story of the participants who contributed, as part of the activity, to the constitution of a theater play aimed at the popularization of science.